Study of the Technique and of the Materials of a 19th‐Century Polychrome Wood Mask from Papua New Guinea. (13th December 2012) - Baraldi, P.; Lo Monaco, A.; Ortenzi, F.; Pelosi, C.; Quarato, F.; Rossi, L.
<x xml:space="preserve">Abstract</x> This paper presents the results of the analysis carried out on a polychrome wood mask from Papua New Guinea during conservation work at Pigorini Museum's restoration laboratory. The significance of this study is that no prior work has characterized the painting materials of Papua New Guinea masks both with spectroscopic and internal microstratigraphic analysis. In fact, these objects were studied especially from an anthropological or conservative point of view and the wood was wrongly defined by its visual appearance. Microstratigraphic and spectroscopic investigations discovered a refined execution technique that up to now has not been demonstrated. The stratigraphy of the painted layers demonstrates a deep knowledge of the materials and of the application techniques on the part of the Papua New Guinea people, together with the ability to foresee the aesthetic result for the artefact. The analysis of the constitutive materials and of the stylistic features supplied valid results in favour of provenance of the mask from Papua New Guinea.